Caracterización fenotípica y genotípica de factores de virulencia de cepas de Escherichia coli uropatógena productora de carbapenemasa - Ramos-Nolazco, Gabriela Alessandra (2025)
Introduction. Uropathogenic Escherichia coli (UPEC) is the leading cause of urinary tract infections (UTIs). Its carbapenem-resistant form (UPEC-rC) harbors specific virulence factors that further limit therapeutic options. Objective. Identify virulence factors in UPEC-rC isolates recovered from urine samples of patients with UTIs in Lima, Peru. Methods. We conducted a descriptive observational study including 58 UPEC-rC isolates. Virulence factors were analyzed in the laboratory: phenotypically (hemolysin on blood agar, P fimbriae by erythrocyte hemagglutination and biofilms production using the microtiter plate method) and genotypically (α-hly, papGII, aer, cnf1, sfa/focDE) by PCR. Results. 28 out of 58 isolates exhibited at least one virulence factor. Genotypically, aer gene was the most frequent (34,5%), while phenotypically, biofilm formation predominated (17,2%). Conclusion. The frequency of aer gen and biofilm production suggests a possible relationship between carbapenem resistance and the attenuation of pathogenic mechanisms.